Detection And Characterization Of Chicken Anemia Virus Isolated From Commercial Broiler Breeder Farms In Malaysia - Negasi, Zerihun Hailemariam (2008)

(untitled)
Chicken anemia virus (CAV) is the causative agent of chicken infectious anemia (CIA). It is an economically important pathogen with a world-wide distribution. Study on the type of CAV isolates present and their genetic diversity, transmission to their progeny and level of protection afforded in the breeder farms is lacking in Malaysia. Hence, the present study was aimed to detect CAV from commercial broiler breeder farms using molecular, serological and immunohistochemical methods and characterize CAV positive samples based on sequence and phylogenetic analysis of partial VP1 gene. In the present study CAV DNA was detected in all 60 commercial broiler breeder hens obtained from 12 farms in three states of Malaysia. Results from ELISA also showed that 96.15% of blood samples collected from the same farms were positive for antibody against CAV supporting the finding from the nested PCR assay. Both of these findings indicate that CAV is widespread in commercial broiler breeder hens at least in the three states of Malaysia. Testing pooled embryonic tissue samples consisting of thymus, bursa of Fabricius and spleen together with egg shell membrane (ESM) showed positive embryos for CAV DNA in the range of 40% to 100% for different commercial broiler breeder farms despite the presence of neutralizing antibodies in majority of the hens (96.15%) tested for CAV antibodies. This shows high level of occurrence of vertical transmission of viral DNA to the progeny. The CAV antigen was also detected in the lymphocytes within the cortex of the thymus and in the hemocytoblasts of the bone marrow by indirect immunoperoxidase staining in some birds. The analysis of 165 amino acid portion of the VP1 protein of 12 isolates from commercial broiler breeder farms revealed unique amino acid residues proline (P) at amino acid position 22 and glutamine (G) at amino acid position 48 in isolates NF4A and PYT4, respectively. Generally, isolates from the commercial broiler breeder farms can be grouped into two based on their amino acid profile at positions 75, 97, 139 and 144. Seven of the isolates (NF4A, PPW4, P24A, P12B, M3B5, MF3C and MF1A) from the commercial broiler breeder farms had 75-I, 97-L, 139-Q and 144-Q and clustered together in cluster IIIa of the deduced amino acid phylogenetic tree whilst the remaining five isolates (M1B1, NF1D, NF2C, NF3A and PYT4) had similar 75-V, 97-M, 139-K and 144-E profile and found in cluster I and II of the deduced amino acid phylogenetic tree. When compared with previously published local field isolates, six isolates from the commercial broiler breeder farms (MF1A, MF3C, M3B5, NF4A, P12B and P24A) were found to have maximum homology with SMSC-1 isolate, four isolates (M1B1, NF3A, PYT4 and PPW4) were found to have maximum homology with BL-5 isolate and the remaining two (NF1D and NF2C) have similar maximum homology both with isolates 3-1 and BL-5. The sequence and phylogenetic analysis further indicated high similarity of current isolates from the commercial broiler breeder farms with isolates in this part of the globe while still having limited variation with isolates from different geographical places. The importance of unique amino acid substitutions observed in this study requires further research in order to identify the detail characteristics of the isolates.